(untitled) (Journal of Additive Manufacturing Technologies, 2021)
Plasma Transferred Arc Welding (PTA) is an important method for efficient component coating. In that field PTA has advantages, such as the free integration and mixing of a variety of filler materials as well as the largely independent material supply in relation to the energy input. Increasingly, the market is being driven by the challenge of providing efficient, high-performance, and safe coatings of complex geometries and components with flexible material depositions, as well as increasing the deposition rate. These tasks are fulfilled by the systematic coupling of two plasma transferred arc welding systems to form a tandem PTA system. Both PTA torches are positioned in such a way that they act in a common melt pool. In previous research it was provided that, deposition rate is 140 % increased with tandem PTA method in comparison to classical single torch PTA coating method. In this research, a direct comparison with classical single torch PTA with parallel driven tandem PTA for additive manufacturing was done. The additive deposition capacity of tandem PTA is 56 % higher than classical PTA for specified time.